Stretch‐Healable Molecular Nanofibers. Issue 10 (18th August 2020) - Han, Yanxiao; Langer, Michal; Medved', Miroslav; Otyepka, Michal; Král, Petr
Abstract: Ultrastretchable nanofibers formed by covalently linked molecular flakes are introduced. Molecular dynamics simulations show that mixed coronene and perfluorocoronene molecular flakes in aqueous solutions form linear stacks having predominantly an alternating pattern. When such molecular flakes are covalently connected by short flexible molecular linkers into chains of various organizations, they can form stretchable and healable fibers with parameters dependent on humidity. Abstract : Molecular dynamics simulations show that mixed coronene and perfluorocoronene molecular flakes in aqueous solutions form linear stacks having predominantly an alternating pattern. Quantum calculations are performed to study coupling energies between flakes. Ultrastretchable nanofibers are designed by covalently connecting flakes using short flexible molecular linkers with parameters dependent on humidity.